2004
DOI: 10.1152/japplphysiol.00452.2004
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline reduces fibrin deposition and prolongs survival in neonatal hyperoxic lung injury

Abstract: Bronchopulmonary dysplasia is a leading cause of mortality and morbidity in preterm infants despite improved treatment modalities. Pentoxifylline, a phosphodiesterase inhibitor, inhibits multiple processes that lead to neonatal hyperoxic lung injury, including inflammation, coagulation, and edema. Using a preterm rat model, we investigated the effects of pentoxifylline on hyperoxia-induced lung injury and survival. Preterm rat pups were exposed to 100% oxygen and injected subcutaneously with 0.9% saline or 75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
2

Year Published

2005
2005
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 43 publications
3
31
0
2
Order By: Relevance
“…Beneficial effects of PTX treatment on survival have been reported in sepsis and in HILI models (21,34). Our study demonstrated survival improvement from 54% to 88% with PTX.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Beneficial effects of PTX treatment on survival have been reported in sepsis and in HILI models (21,34). Our study demonstrated survival improvement from 54% to 88% with PTX.…”
Section: Discussionsupporting
confidence: 73%
“…The twice-a-day dosing used in this experiment might have not been optimal to exert all the potential benefits of PTX in the lungs of the newborn. However, this dosing was already found to be safe in preterm rats and beneficial in HILI as reported by ter Horst et al (21). Second, the animals most susceptible to oxygen-induced injury were not analyzed due to their death.…”
Section: Ptx In Neonatal Hyperoxic Lung Injurymentioning
confidence: 96%
See 2 more Smart Citations
“…Ter Horst et al mostraram que a pentoxifilina, uma metilxantina com efeito modulador, reduz o depósito de fibrina e aumenta a sobrevida de ratos recém-nascidos expostos à hiperóxia 78 . Trabalhos experimentais em nosso laboratório mostram que a pentoxifilina atenua o aumento dos mediadores inflamató-rios e, também, o edema pulmonar, após ventilação com volumes correntes elevados em ratos 79 .…”
Section: Futuras Terapiasunclassified